MODELLING A SUSTAINABILITY MODEL OF ISLAMIC MICROFINANCE INSTITUTIONS - Sari, Yuli Indah; bin Mislan Cokrohadisumarto, Widiyanto (Journal of Islamic Monetary Economics and Finance, 2019)
Islamic microfinance institutions (IMFIs) – such as Baitul Maal wat Tamwil (BMT - withcooperative legal entities), established in Indonesia as part of the shariah-compliantfinancial industry sector (part of the halal sector) – need to maintain their sustainabilityin order to encourage poverty alleviation and economic growth. In observing thesustainability of BMT, there has been relatively little research involving aspects of thequality of the human resources that carry out internal activities. Therefore, the aim ofthis study is to create a model that is useful for predicting the sustainability of IMFIs,especially BMT, based on variables that are considered important, namely financinggrowth, Islamic human capital, fraud and Islamic leadership. The model was analysedusing multiple regression analysis based on the stepwise method. The primarydata (cross-sectional) were obtained in 2019 using questionnaires completed by 105respondents comprising the administrators and managers of BMTs in Semarang andPekalongan, Central Java, Indonesia. We found that only two variables have a significantinfluence on the sustainability of IMFIs: financing growth and Islamic human capital.Practitioners can apply the results of the study to improve the performance of Islamicmicrofinance, especially BMT, through the distribution of funding in the context ofeconomic improvement (especially micro-enterprise), spiritual strengthening forhuman resources, risk prevention and appropriate leadership criteria.